Discordant K‐Ar and young exposure dates for the Windjana sandstone, Kimberley, Gale Crater, Mars. Issue 10 (27th October 2016) - Vasconcelos, P. M.; Farley, K. A.; Malespin, C. A.; Mahaffy, P.; Ming, D.; McLennan, S. M.; Hurowitz, J. A.; Rice, Melissa S.
Abstract: K‐Ar and noble gas surface exposure age measurements were carried out on the Windjana sandstone, Kimberley region, Gale Crater, Mars, by using the Sample Analysis at Mars instrument on the Curiosity rover. The sandstone is unusually rich in sanidine, as determined by CheMin X‐ray diffraction, contributing to the high K2 O concentration of 3.09 ± 0.20 wt % measured by Alpha‐Particle X‐ray Spectrometer analysis. A sandstone aliquot heated to ~915°C yielded a K‐Ar age of 627 ± 50 Ma. Reheating this aliquot yielded no additional Ar. A second aliquot heated in the same way yielded a much higher K‐Ar age of 1710 ± 110 Ma. These data suggest incomplete Ar extraction from a rock with a K‐Ar age older than 1710 Ma. Incomplete extraction at ~900°C is not surprising for a rock with a large fraction of K carried by Ar‐retentive K‐feldspar. Likely, variability in the exact temperature achieved by the sample from run to run, uncertainties in sample mass estimation, and possible mineral fractionation during transport and storage prior to analysis may contribute to these discrepant data. Cosmic ray exposure ages from 3 He and 21 Ne in the two aliquots are minimum values given the possibility of incomplete extraction. However, the general similarity between the 3 He (57 ± 49 and 18 ± 32 Ma, mean 30 Ma) and 21 Ne (2 ± 32 and 83 ± 24 Ma, mean 54 Ma) exposure ages provides no evidence for underextraction. The implied erosion rate at the Kimberley location is similar to that reported at the nearby Yellowknife Bay outcrop. Key Points: Second in situ dating on Mars using SAM in MSL K‐Ar age discrepant Cosmogenic isotope ages young and internally compatible